Nutritional status and appetite-regulating hormones in early treatment of acute lymphoblastic leukemia among children and adolescents: a cohort study - Gomes, Camila de Carvalho; Silva, Cassia Camila Gomes da; Nascimento, Paulo Ricardo Porfírio do; Lemo, Telma Maria de Araújo Moura; Marcadenti, Aline; Markoski, Melissa Medeiros; Fayh, Ana Paula Trussardi (São Paulo Medical Journal, 2020)
BACKGROUND: Children with acute lymphoblastic leukemia are at risk of malnutrition, but few studies have described the changes in nutritional status during the different phases of chemotherapy. OBJECTIVE: To evaluate changes in nutritional status, food intake and appetite-regulating hormones among children and adolescents with acute lymphoblastic leukemia in the first phase of chemotherapy. DESIGN AND SETTING: Cohort study developed in the pediatric oncology departments of two hospitals in the city of Natal, Rio Grande do Norte, Brazil. METHODS: Fourteen children/adolescents (mean age of 7 years; 50% female) with acute lymphoblastic leukemia were monitored over the 28 days of an induction chemotherapy cycle. Anthropometric measurements, 24-hours food weight records and appetite-regulating hormone levels (ghrelin, leptin, insulin and cortisol) were obtained at three different times (before, in the middle and at the end of the induction phase). RESULTS: Most of the patients (85.7%) had normal weight at the beginning of the treatment, and this did not change significantly during the 28 days. Energy and nutrient intakes improved from the start of the treatment to the midpoint, according to the ghrelin levels (from 511.1 ± 8.3 to 519.3 ± 6.6 pg/ml; P = 0.027). Other appetite-regulating hormones did not present changes. CONCLUSION: Food consumption improves during the first phase of treatment, without alterations in anthropometric nutritional status.